PERAN KETOKOHAN, IKATAN EMOSIONAL DAN PROGRAM KERJA DALAM MEMENGARUHI PERILAKU MEMILIH (PENDEKATAN PEMASARAN POLITIK DALAM PEMILIHAN CALON KEPALA DESA) - Suwignyo Widagdo (UPT Penerbitan Universitas Jember)
The purpose of this study is to determine the effect persona, emotional ties and work program on the behavior of selecting candidates for village chief. The population in this study is that people who have a right to vote on the object of research, while the sample of 120 people. This research includes studies explanatoris (explanatoris research). The analysis tool used is multiple linear regression, t test and F test results of this study concluded that persona, emotional ties and work program affect voting behavior. The work program is the dominant variabel in the decision to choose. The results of this study indicate that there has been a shift in voting behavior, causing volatility in the selection of candidates to the village. Research results have broad implications for the winning strategy which must be formulated in accordance with the character of the voters.